2006
DOI: 10.1111/j.1461-0248.2006.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf herbivory and nutrients increase nectar alkaloids

Abstract: Correlations between traits may constrain ecological and evolutionary responses to multispecies interactions. Many plants produce defensive compounds in nectar and leaves that could influence interactions with pollinators and herbivores, but the relationship between nectar and leaf defences is entirely unexplored. Correlations between leaf and nectar traits may be mediated by resources and prior damage. We determined the effect of nutrients and leaf herbivory by Manduca sexta on Nicotiana tabacum nectar and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
187
4
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 170 publications
(200 citation statements)
references
References 59 publications
7
187
4
2
Order By: Relevance
“…Several aspects of the relationship between herbivory and nectar production have been studied. Some studies have pointed out a possible connection between herbivore activity and nectar production, through changes in sugar and alkaloid concentrations (Strauss 1997;Adler et al 2006). Moreover, showed that petal feeding of Isomeris arborea by the beetle Meligethes rufimanus caused a significant decline in nectar production by a factor of up to 3, compared with undamaged flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Several aspects of the relationship between herbivory and nectar production have been studied. Some studies have pointed out a possible connection between herbivore activity and nectar production, through changes in sugar and alkaloid concentrations (Strauss 1997;Adler et al 2006). Moreover, showed that petal feeding of Isomeris arborea by the beetle Meligethes rufimanus caused a significant decline in nectar production by a factor of up to 3, compared with undamaged flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, studies of plant-herbivore and plant-pollinator interactions have focused either on pollinator attraction to floral traits or herbivore deterrence by plant defenses. However, most plants interact simultaneously with a variety of pollinators and herbivores that could exert reinforcing or conflicting selection pressure on plant traits (Strauss and Whittall 2006;Adler 2007) The study of pair-wise interactions in isolation may not give us an adequate understanding of the costs and benefits of phenotypic traits that mediate interactions with both herbivores and pollinators (Gomez and Zamora 2000;Herrera 2000;Adler et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies determined 0.1-0.5 ”g/mL and 0.6-5 ”g/mL as the concentration range of nicotine and anabasine, respectively, in the nectar of N. glauca [57]; whereas in N. tabacum 0.33 ”g/mL was measured as the concentration of nicotine and anabasine [3]. In the nectar of N. attenuata the concentration of nicotine was 3 ± 0.35 ”g/mL [13].…”
Section: Alkaloid Content Of the Floral Nectarmentioning
confidence: 99%